Cooling During Exercise May Induce Benefits Linked to Improved Brain Perfusion - Douzi, Wafa; Dugué, Benoit; Theurot, Dimitri; Vinches, Ludwig; Hallé, Stéphane; Dupuy, Olivier (International Journal of Sports Medicine, 2020)
The aim of this study was to evaluate the impact of using a cooling vest during physical exercise (per-cooling) in humid and temperate conditions (≈22°C, ≈80% relative humidity) on perceptual and physiological responses (tissue oxygenation and heart rate). 20 physically active men performed twice a 30-min cycling exercise at 70% of their theoretical maximum heart rate while using an activated (experimental condition) and a deactivated (control condition) cooling system in a randomized crossover study. Heart rate and tissue (cerebral and muscular) oxygenation were continuously measured during exercise and recovery, and skin temperature was measured every 10 min. Perception of temperature, humidity and comfort were assessed at the end of the recovery period. Results showed a decrease in trunk skin temperature (p<0.05), a faster heart rate recovery and an increase in the concentration of total hemoglobin at the brain level (p<0.05) compared with control condition. Moreover, an improved subjective rating of thermal sensations, wetness and comfort compared to control values (p<0.05) was noted. In conclusion, wearing a cooling vest during submaximal exercise improves perceptual and physiological responses in humid temperate conditions, which may be due to a better blood perfusion at the brain level and a better parasympathetic reactivation.
Keywords: cooling device; brain perfusion; exercise; thermoregulation; per-cooling